O06.6 The urethral microbiota in nongonococcal urethritis. (8th July 2017) - Srinivasan, Sujatha; Chambers, Laura; Hoffman, Noah G; Morgan, Jennifer L; Munch, Matthew M; Yuhas, Krista; Lowens, M Sylvan; Proll, Sean; Hughes, James P; Fredricks, David N; Manhart, Lisa E
Abstract : Introduction: There is no known aetiology for up to half of all nongonococcal urethritis (NGU) cases. We sought to characterise the bacterial communities in men with (NGU+) and without (NGU-) NGU among men who have sex with men (MSM) and men who have sex with women (MSW), to determine if the urethral microbiota is associated with NGU status. Methods: From December 2014 to December 2015, urine samples were collected from 49 MSM (23 NGU+; 26 NGU-) and 48 MSW (21 NGU+; 27 NGU-) attending the Seattle STD Clinic. NGU was defined as urethral symptoms and/or visible discharge, and >5 PMNs per high powered field. Chlamydia trachomatis (CT) and Mycoplasma genitalium (MG) were detected by transcription mediated amplification (TMA). The urethral microbiota was characterised using broad-range 16S rRNA gene PCR with deep sequencing. Bacterial diversity was calculated using the Shannon index. Results: Mean urethral bacterial diversity in NGU+ MSM (0.82) was lower than in NGU- MSM (1.48), Streptococcus (n=7), Corynebacterium (n=5), Haemophilus (n=3), Mycoplasma (n=3), and Lactobacillus iners (n=2). Urethral microbiotas with dominant taxa were more common in NGU+ MSM (95.7%), while NGU+ MSW (61.9%) had microbiotas characterised by the presence of several vaginal bacteria. Among NGU- men, 53.8% MSM and 48.1% MSW had microbiotas with dominant taxa, including Streptococcus (n=19), L. iners (n=5), and Gardnerella vaginalis (n=4). Conclusion: The urethral microbiota in NGU is heterogeneous. NGU- MSM had more diverse urethral bacterial communities than NGU+ MSM, and presence of vaginal bacteria in MSW suggests sharing or acquisition from female partners. Future longitudinal studies may help inform if key bacteria predict incident NGU.